Pengaruh Lingkungan Kerja dan Komitmen Organisasi terhadap Niat Turnover Karyawan di PT Bersatu Meraih Sukses (MR REALTY) - Anggi Anggiansyah; Yusuf Supardi (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
This study aims to analyze the effect of Work Environment and Organizational Commitment on Employee Turnover Intention at PT Bersatu Meraih Sukses (MR Realty), both partially and simultaneously. The research employed a quantitative associative method. Data were collected through questionnaires distributed to 90 employees and analyzed using simple and multiple linear regression with SPSS version 27. Hypothesis testing was conducted using t-tests and F-tests. The results indicate that the Work Environment has a positive and significant effect on Employee Turnover Intention, with a t-value of 7.644 greater than the t-table value of 1.988. Organizational Commitment also has a positive and significant effect on Employee Turnover Intention, with a t-value of 6.137 exceeding the t-table value of 1.988. Simultaneously, both independent variables significantly influence Employee Turnover Intention, as evidenced by an F-value of 124.847, which is greater than the F-table value of 3.10, with a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.742 indicates that Work Environment and Organizational Commitment contribute 74.2% to the variation in Employee Turnover Intention, while the remaining 25.8% is explained by other variables outside this study.